2020
DOI: 10.1073/pnas.1902298117
|View full text |Cite
|
Sign up to set email alerts
|

Ddi1 is a ubiquitin-dependent protease

Abstract: TheSaccharomyces cerevisiaeprotein Ddi1 and its homologs in higher eukaryotes have been proposed to serve as shuttling factors that deliver ubiquitinated substrates to the proteasome. Although Ddi1 contains both ubiquitin-interacting UBA and proteasome-interacting UBL domains, the UBL domain is atypical, as it binds ubiquitin. Furthermore, unlike other shuttling factors, Ddi1 and its homologs contain a conserved helical domain (helical domain of Ddi1, HDD) and a retroviral-like protease (RVP) domain. The RVP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 46 publications
3
83
0
Order By: Relevance
“…Intersects indicated in Figure 6A by arrows, are the subunits of the proteasome core, showing the strength of using mTPP in multiomics intersection analysis for identifying candidate protein subsets involved in the mechanism behind an observed phenotype. Aside from the core proteasome subunits, the additional member within this subset is the DNAdamage inducible protein 1 (Ddi1), a ubiquitin binding protein that functions as a proteasome shuttle (reviewed in (87)) that has recently been characterized as a ubiquitin-dependent protease (88). Ddi1 is destabilized in rpn5-ts as well (Supp.…”
Section: Multiomics Intersection Analysis Of Mtpp With Global Proteommentioning
confidence: 99%
“…Intersects indicated in Figure 6A by arrows, are the subunits of the proteasome core, showing the strength of using mTPP in multiomics intersection analysis for identifying candidate protein subsets involved in the mechanism behind an observed phenotype. Aside from the core proteasome subunits, the additional member within this subset is the DNAdamage inducible protein 1 (Ddi1), a ubiquitin binding protein that functions as a proteasome shuttle (reviewed in (87)) that has recently been characterized as a ubiquitin-dependent protease (88). Ddi1 is destabilized in rpn5-ts as well (Supp.…”
Section: Multiomics Intersection Analysis Of Mtpp With Global Proteommentioning
confidence: 99%
“…When cells are challenged with an excess of DPCs, they may require an alternative DPC protease. Ddi1 and 26S proteasome could at least partially substitute for Wss1 function (Serbyn et al, 2020), and both of them target ubiquitinated proteins for degradation (Finley et al, 2012;Yip et al, 2020). Ubiquitin and SUMO are known to compete for the acceptor lysines (Hendriks et al, 2014).…”
Section: Deleterious Effects Of Siz2-dependent Sumo Conjugation On Tomentioning
confidence: 99%
“…Indeed, it would in many ways make sense in the context of the role of Ddi1/DDI2 as ubiquitin shuttles if infrequent cleavage of long ubiquitin chains facilitated the loading into the proteasome of a large variety of proteins with long ubiquitin chains. Interestingly, while this manuscript was in revision, Rapoport and co-workers reported complementary data that showed that the yeast Ddi1 protein preferentially (or exclusively) recognizes an artificial target protein when it carries a long ubiquitin chain and that it may even weakly cut the chain itself ( Yip et al., 2020 ). Importantly, our results clearly indicate that proteins with very long ubiquitin chains are slowly degraded by the UPS and require DDI2 activity for their timely removal in vivo .…”
Section: Introductionmentioning
confidence: 99%